2020
DOI: 10.1186/s13256-020-2353-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary aldosteronism concurrent with subclinical Cushing’s syndrome: a case report and review of the literature

Abstract: Background: The prevalence of primary aldosteronism concurrent with subclinical Cushing's syndrome was higher than previously thought. Through analyzing a rare clinical case, we summarized the diagnosis and management of primary aldosteronism with subclinical Cushing's syndrome. Case presentation: A 54-year-old Chinese man of Han nationality was diagnosed as having primary aldosteronism with subclinical Cushing's syndrome. An abdominal computed tomography scan revealed a mass in his left adrenal gland and a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…They measured the concentrations of plasma epinephrine in both AV and IVC to enable adjustment in the present patient. Yingxiao Zhang et al ( 22 ) reported a PA and SCS case of bilateral adrenal tumors, in which the left adrenocortical tumor produced cortisol and the right one secreted aldosterone. The diagnosis was supported by endocrine findings, AVS and immunohistochemical evaluation of steroidogenic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They measured the concentrations of plasma epinephrine in both AV and IVC to enable adjustment in the present patient. Yingxiao Zhang et al ( 22 ) reported a PA and SCS case of bilateral adrenal tumors, in which the left adrenocortical tumor produced cortisol and the right one secreted aldosterone. The diagnosis was supported by endocrine findings, AVS and immunohistochemical evaluation of steroidogenic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…SCS is generally found when a patient with an unidentified adrenal mass underwent DMST, and it is the most common endocrine syndrome associated with an adrenal adenoma ( 22 , 24 ). Many cases of PA with SCS have been reported as aldosterone/cortisol cosecreting adenomas ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from Zhang et al. raised the concern that PA patients should have low-dose overnight DST to rule out the existence of concurrent ACS and to avoid misinterpretations of AVS results that may lead to suboptimal managements of the patients postoperatively due to the emergence of temporary hypocortisonism in patients with preoperative concurrent ACS ( 27 ). Given the significant prevalence of uPA patients with cortisol co-secretion, our evidence also supports the practice that all uPA patients should have their baseline 1 mg DST measured to not only help predict surgical outcomes, but to also inform suitable postoperative steroid supplement and tapering regimens for the prevention of adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Primary aldosteronism with subclinical Cushing's syndrome used to be thought as a rare disease 1,2 . However, with the recent substantial increase in the diagnosis of primary aldosteronism, there was an increase in the reporting of cases with the coexistence of primary aldosteronism and subclinical Cushing's syndrome 3,4,5,6,7 . Although subclinical Cushing's syndrome often has no clinical manifestations, its coexistence with primary aldosteronism is clinically relevant for the diagnosis and treatment of the latter disease.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, with the recent substantial increase in the diagnosis of primary aldosteronism, there was an increase in the reporting of cases with the coexistence of primary aldosteronism and subclinical Cushing's syndrome. 3 , 4 , 5 , 6 , 7 Although subclinical Cushing's syndrome often has no clinical manifestations, its coexistence with primary aldosteronism is clinically relevant for the diagnosis and treatment of the latter disease. The lateralization of primary aldosteronism relies on the contrast of the aldosterone and cortisol concentrations.…”
Section: Introductionmentioning
confidence: 99%